Analysis and application of stress distribution in 24-m high bench loosening blasting with axially uncoupled charge structure in Barun Open-pit Mine. Issue 2 (July 2021) - Yin, Zuoming; Wang, Xuguang; Wang, Desheng; Dang, Zhiheng; Bi, Jiahao
Abstract: The Barun Open-pit Mine has formed a 2-benches or 4-benches parallel mining condition due to the steep end-slope mining. In the enlarging process, the operation safety conditions of equipment are poor. In order to improve the operating conditions, increase the efficiency of slope enlarging, and reduce the mining cost, a technical solution is proposed that uncoupling the top air-deck charge structure by loosening blasting in the 24-m high bench. Based on the Holmquist-Johnson-Cook (HJC) constitutive model, the physical mechanism of the stress wave attenuation in the rock is analyzed. Considering the attenuation, reflection, transmission, and superposition of the pressure produced by the charge, the stress of any point in the rock medium is calculated. Furthermore, the rock state at that point is judged. The results show that the top air-deck reduces the stress at the top of the slope. Although the top resistance line is smaller than the bottom of the slope, with the top air-deck, the rock stress state at the top of the slope is not much larger than the bottom charge section, which makes the rock loose and does not produce a throwing phenomenon. After blasting, the muck pile has a good shape. The top air-deck charge structure has obvious effects in loose blasting, which provides a practical exploration for the slope enlarging of high benches in open-pit mines.